Organoleptic Test and Analysis of Vitamin C Content of Red Snake Fruit Jelly (Salacca edulis Reinw) - Alwi Smith; Ritha Karuwal; Kristin Sangur; Eifan Boyke Pattiasina; Rufiati Simal (BIOPENDIX, 2025)
In Maluku, the salak center is on Ambon Island, namely Soya, Hatalai, Wakal, Amahusu, and Hative Besar Villages, and also on Seram Island, namely Piru, Taniwel, Riring Villages. Salak in West Seram Regency is one of the native salak cultivars of Maluku. This is because this cultivar has a red fruit appearance and a sweet and sour taste. Organoleptic of red snake fruit jelly candy on the color parameter the highest value on a scale of 4 with a total of 11 panelists, who really like the brownish red color with an average of (3.92), the taste parameter the highest value on a scale of 4 with as many as 16 panelists who like the sweet taste typical of red snake fruit with an average of (4.00), the aroma parameter the highest value on a scale of 4 as many as 10 panelists who like the fragrant aroma typical of red snake fruit, with an average of (3.60), the texture parameter the highest value on a scale of 5 as many as 12 panelists who like a very soft and chewy texture, with an average of (4.12) and the average vitamin C content in red snake fruit jelly candy is 4.58 mg/100g.